A Melatonin Treatment Delays Postharvest Senescence, Maintains Quality, Reduces Chilling Injury, and Regulates Antioxidant Metabolism in Mango Fruit. (31st January 2022) - Bhardwaj, Renu; Pareek, Sunil; Mani, Saravanan; Domínguez-Avila, J. Abraham; González-Aguilar, Gustavo A.
Abstract : The effects of an exogenous application of various concentrations and dipping duration of melatonin (MT) treatment on postharvest senescence, quality, chilling tolerance, and antioxidant metabolism of mango fruit cv. "Dashehari" were examined. Fruits were treated with three concentrations of MT (50, 100, or 150  µ M), each applied for three times (60, 90, or 120 min), followed by storage at 5 ± 1°C. The MT concentration of 100  µ M with a dipping duration of 120 min was efficient in reducing the chilling injury and maintaining the quality of mango fruit for 28 d. Effects of this treatment were due to its effectiveness in reducing metabolic activity, specifically, respiration rate and ethylene production, resulting in higher firmness, titratable acidity, and ascorbic acid content and lower weight loss, total soluble solids, pH, and total soluble solid : acidity ratio. Moreover, it maintained a higher concentration of total phenolics and total flavonoids, as well as antioxidant capacity (2, 2-diphenyl-1-picrylhydrazyl and cupric reducing antioxidant power assays), as compared to other treatments. This was further confirmed with higher activities of antioxidant enzymes superoxide dismutase and catalase and membrane stability (according to a lower malondialdehyde content and lipoxygenase activity). Thus, our data show that a 100  µ M MT administered for 120 min appears to be the most appropriate treatment to maintain the quality of mango fruits stored at chilling temperatures.